The Relationship Between Skeletal Muscle Exercise and Immune Endurance: A Literature Review - Ahmad Rajendra Paturusi; Jamaluddin Jamaluddin; Muh. Abdillah Burhan; Firda Amelia Ajis Dini; Dihan Julianto (International Journal of Experimental Sports Science Research, 2025)
Background: Skeletal muscle functions not only as a locomotor organ but also as an active endocrine organ that produces myokines  bioactive peptides with pleiotropic effects on the immune system. Understanding the relationship between skeletal muscle exercise and immune endurance is increasingly relevant amid rising infectious diseases and declining immunity in physically inactive populations. Objectives: This literature review aimed to synthesize and analyze current scientific evidence on the mechanistic relationship between skeletal muscle exercise and immune endurance, encompassing molecular pathways involved, effects of exercise on cellular and humoral immune components, and the implications of exercise dose on immune response. Methods: A systematic literature search was conducted on PubMed, Scopus, Google Scholar, and ScienceDirect using keywords: skeletal muscle exercise, immune system, myokines, immunomodulation, physical activity, and inflammation. Inclusion criteria covered original research articles and reviews published between 2015–2025 in English and Indonesian. Twenty-three articles met criteria for narrative analysis. Results: Moderate-intensity skeletal muscle exercise consistently enhances immune function through: (1) production and secretion of myokines  particularly IL-6, IL-15, irisin, and BDNF  which modulate NK cell, T cell, macrophage, and neutrophil activity; (2) regulation of systemic inflammation through reductions in TNF-α, IL-1β, and CRP; (3) increased leukocyte circulation and phagocytic capacity; and (4) improved mucosal barrier function and secretory IgA production. Conversely, very high-intensity prolonged exercise without adequate recovery induces transient immunosuppression through elevated cortisol and decreased lymphocyte ratio. Conclusions: Moderate-intensity skeletal muscle exercise with appropriate frequency and duration is an effective natural immunomodulator. Understanding optimal exercise dose is critical to maximizing immunological benefits while avoiding immunosuppression risk.